The role of the sociological communities of Russia and Kazakhstan in the integration and cooperation of two states - R E Sagindikov (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2014)
The article analyzes various practices of cooperation between Russian and Kazakhstani sociologists, identifies its most significant stages on the macro-level, i.e. the institutional level. The author also characterizes the national sociological association of Kazakhstan (ASK), specifies its contacts with major Russian sociological associations. The author underlines that the sociologies and sociological communities of two largest CIS countries - Russia and Kazakhstan - study the fundamental problems of integration processes and develop new approaches and projects of cooperation.